George D. Prentice and the Whig Sense of Humor. - Burge, Daniel J. (Studies in American Humor, 2022)
Scholars have recently begun reexamining the Whig Party, paying particular attention to how the party gained adherents and challenged Andrew Jackson and his acolytes. Yet few scholars have focused attention on the Whig sense of humor. Typically portrayed as more uptight than their rambunctious Democratic counterparts, Whigs were seemingly unable to find humor in a burgeoning democratic society. This article challenges that traditional portrait by examining George D. Prentice, the long-serving editor of the Louisville Journal. Although largely forgotten as a humorist, Prentice gained a national reputation for his "hits" that appeared daily in the pages of the Louisville Journal from 1830 to 1868. By pillorying the opposition party, Prentice found a way to joke about corruption, adultery, drunkenness, and even death. In doing so, Prentice proved that Whigs did have a sense of humor, although it largely consisted of mocking Democrats for their eccentricities and supposed moral failings.